Level of Teaching Practices in Mathematics in Relation to Indigenous Students’ Academic Performance in Selected Schools in Zambales SY 2019-2020 - Panes, Annalou B.; Falle , Teresita A. (Future Science / FSH-PH Publications, 2021)
The study revealed that the teacher-respondent is in her early adulthood, bachelors’ degree holder and attended few numbers of training relevant to teaching IP students. The teacher-respondents assessed “Always Practiced” on the dimensions of teaching Mathematics strategies among IP students. The students assessed “Always Practiced” on the dimensions of teaching Mathematics strategies among IP students. The IP students were rated “Satisfactory” in both Mathematics subjects Algebra and Geometry. There is significant difference on the perception towards dimensions on teaching Mathematics strategies for IP students between teachers and students. There is significant difference on the perception of the teacher-respondents while no significant differences to the students towards dimensions of teaching Mathematics strategies among IP students as to Creating Student’s Learning Environment Focused on Mathematics Goals, Providing Opportunities for Independent and Collaborative, Facilitating Mathematical Discussion, Using Appropriate Mathematics Language, connections, tools, and presentations, Developing and Using Teacher Knowledge to Initiate Learning and Assessing Student Academic Performance in Algebra and Geometry. The researcher offered the following recommendations based in the study that the school management is encouraged to organize an in-house teacher’s capability training in order to enhance motivational techniques and teaching strategies in Mathematics among IP students; the teachers are encouraged to be resourceful and creative in organizing the lesson in order to unlock the difficulty among the students in learning mathematics; the teachers are encouraged to conduct and in-depth study on the nature of the students and apply the learning activity and exercises based on their capability and competence.